Timely determining and preventing conflict situations between investors and third parties: some observations from Lithuania - Šostak, Olga Regina; Makutėnienė, Daiva (International Journal of Strategic Property Management, 2013)
The article analyses the possible influence of third-party rights infringed during construction planning on the implementation of an investment project. It analyses the process for defence of third party rights infringed during territorial planning. The focus in this process is on third party rights and opportunities to learn about possible infringement of such rights. In a construction project, judicial disputes are an unwanted risk factor, which may disrupt the entire project. It is therefore necessary to plan and apply preventive measures for the mitigation of such risk at the initial planning stage of a construction project. For that end, the article presents some principles of behaviour and actions that could help investors and third parties to solve conflicts, reduce their negative outcomes or reach an arrangement satisfactory to both disputing parties. First Publish Online: 19 Dec 2013